The Social Service between Values and Welfare Policies (Il Servizio Sociale tra Valori e Politiche di Welfare) - Francesca D'Atri (Science & Philosophy, 2017)
Main values of social work guide and select the everyday work of professional social worker, within institutional and non-institutional contexts, for people and with people facing different conditions of fragility and poverty, acting more innovative intervention strategies that respond to the real needs of the individual, the family system and, in general terms, the local community.